Optimalisasi Pemberdayaan Masyarakat Melalui Program Waste Berbasis Management Program Untuk Mewujudkan SDG’S Di Desa Leuweungkolot - Syaiful Anwar; Zeze Zakaria Hamzah; Muhlis; Ria Vivian Ramadhani; Dwi Tiara Hardianti; Selfi Septiani; Juwita Aidil Adha (CV. ITTC INDONESIA, 2025)
The Waste program is one of the pillars of Walinghealth, designed to strengthen community-based waste management in Leuweungkolot Village, Cibungbulang Subdistrict, Bogor Regency. The main problems identified in this village include the low level of household waste segregation awareness, limited waste management facilities, and the persistence of illegal dumping practices. To address these issues, the program was implemented through six key strategies: capacity building of the implementing team through waste bank training, socialization of waste segregation, establishment of a TPS3R (Reduce, Reuse, Recycle Waste Processing Site) in RW 06, designation of collection points in several neighborhood units, formation of GASSAH (Gerakan Sadar Sampah Hidup Sehat) as a local driving community, and clean-up activities involving around 20 residents. The results indicate increased community participation, the establishment of local institutions, and the availability of physical infrastructure such as TPS3R and waste collection points. Approximately 100 kg of waste was managed during the initial phase. This program contributes to the achievement of the Sustainable Development Goals (SDGs), particularly SDG 3, SDG 11, and SDG 12.